TRANSFORMASI KONSEP WAHDAT AL-WUJUD IBN ARABI DALAM TASAWUF KONTEMPORER INDONESIA - Karlina, Intan; Gazali, Gazali (UIN Sumatera Utara Medan, 2025)
This study analyzes the transformation of Ibn Arabi's concept of wahdat al-wujud (the unity of being) within the context of contemporary Indonesian Sufism, particularly in response to the challenges of religious pluralism. Employing a qualitative approach and case study method, the research explores how the metaphysical doctrine developed by Muhyiddin Ibn Arabi (1165-1240 CE) has been adapted by modern Indonesian Sufi figures to address the complexities of religious life in the modern era. Data were collected through textual analysis, in-depth interviews with leaders of Sufi orders, and observation of spiritual practices in various pesantren and zawiyah. The findings reveal that wahdat al-wujud has undergone significant reinterpretation, with a particular emphasis on values of tolerance, inclusivity, and interreligious coexistence, while still upholding core Islamic theological principles. This transformation reflects Sufism's capacity to respond to local socio-cultural changes while preserving its spiritual depth. The study contributes to a deeper understanding of the flexibility of classical Sufi teachings in modern contexts and offers a fresh perspective on the role of Sufism in fostering religious harmony and tolerance within Indonesia's pluralistic society.